2008
DOI: 10.1167/iovs.07-1259
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Retina-Specific Expression of the Small Heat Shock Protein, αA-crystallin, Is Associated with Photoreceptor Protection in Experimental Uveitis

Abstract: alphaA-Crystallin is highly upregulated in the retina during early EAU. This upregulation is localized primarily in the photoreceptor inner segments, the site of mitochondrial oxidative stress. Further, in early EAU, the photoreceptors preferentially use alphaA-crystallin to suppress mitochondrial oxidative stress-mediated apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
88
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 60 publications
6
88
1
Order By: Relevance
“…Anti-␣A is a polyclonal antibody raised against the N terminus 12 residues (2-13 of the rat ␣A) (16). Anti-␣B is a polyclonal antibody raised against the C terminus, 13 residues (163-175) of the rat ␣B (14, 15).…”
Section: Fractionation Of Homogenates For Enrichment Of Various Membranementioning
confidence: 99%
“…Anti-␣A is a polyclonal antibody raised against the N terminus 12 residues (2-13 of the rat ␣A) (16). Anti-␣B is a polyclonal antibody raised against the C terminus, 13 residues (163-175) of the rat ␣B (14, 15).…”
Section: Fractionation Of Homogenates For Enrichment Of Various Membranementioning
confidence: 99%
“…Oxidative stress leads to up-regulation of a host of Hsp, including α-crystallins (16). Rao et al demonstrated that photoreceptors selectively up-regulated αA-crystallin against immune-mediated mitochondrial oxidative stress by EAU involving the retina (6). We recently demonstrated that mitochondrial oxidative stress occurs in the photoreceptor inner segment in SO globes of humans (11).…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, in the retina where αA-crystallin immunoreactivity was markedly detected, no TUNEL-positive signals were observed. Rao et al found that αA-crystallin was expressed in the photoreceptors and protected them from apoptotic signals in an EAU model (6). In actuality, αA-crystallin exerts an anti-apoptotic function by blocking pro-apoptotic mitochondrial pathways, thereby inhibiting the activation of downstream apoptotic events (3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations